CLIL: Bridging the Gap Between Language and Content - Soltani, Riad (Central European Journal of Educational Research, 2023)
Bibliography of the reviewed book: Coyle, D., Hood, P., & Marsh, D (2010). CLIL: Content and Language Integrated Learning. Cambridge University Press.